Love and the Pitfall of Moralism - Pacovská, Kamila (Cambridge University Press, 2018)
In what sense does love presuppose appreciation of the other's character? First, I argue that loving appreciation is more often a source of truthful vision than of bias and idealisation. Second, using the example of Elizabeth Bennett, I show that the tendency to forfeit love for those who lose our good opinion can be an expression of undue moralism and pride. Nonjudgmental responses to the other's flaws show how virtuous love can combine both realistic vision of the other's flaws and appreciation of the other that does not stand on balancing flaws with qualities. Such love is in the end connected with a conception of goodness inspired by Kierkegaard and Weil.
Love and the Pitfall of Moralism
Keywords: love; character traits; flaws; partiality; judgmentalism; moralism; superiority; humility; equality; Elizabeth Bennet; láska; charakterové rysy; neřesti; zaujatost; morální odsuzování; moralizování; povýšenost; pokora; rovnost; Elizabeth Bennet